Penser la technique : de l’oubli aux nouveaux eclairages jetes sur des questions anciennes - Tinland, Franck (Mechane, 2020)
While considered for a long time both as the cornerstone of humanity and as subaltern activity as well, technique is nowadays the core of man’s asking about his own future. After having been the reason of a swinging of values, in accordance both with past and future, via the advent of Temps moderns, the development of techniques has been questioned, for the recovery of the finiteness and fragility of inhabitable world. Such a rediscovery prevents us from indefinitely jeopardising those fundamental principles according to which the current forms of the living shaped themselves. This situation compels us to urgently reflect upon the conditions within which technicality is born, grows and becomes autonomous, considering that it snatches humanity away from the rhythms of biosphere, although they still stand in solidarity.